When adaptation increases energy demand: A systematic map of the literature - V Viguié; S Juhel; T Ben-Ari; M Colombert; J D Ford; L G Giraudet; D Reckien (Environmental Research Letters, 2021)
Adaptation is a central component of climate policy, helping manage and reduce risks. Sometimes, however, adaptation to climate change may consume energy, threatening efforts to reduce greenhouse gas emissions. Examples are numerous, and include the use of air conditioning or water desalination. Nevertheless, no clear view exists on how energy demand globally can be impacted by climate change. In this paper we systematically map existing evidence on how and to what extent adaptation responses to climate change may impact energy demand. The literature is large, fast-growing and spans several disciplines, but we identify several research gaps. First, the literature focuses almost exclusively on heating and cooling demand, while overlooking other potential sectors. It also focuses heavily on a few world regions, while local specific climate and socio-economic conditions may highly influence the impacts, and focuses largely on average demand, while often disregarding peak energy demand. Finally, and most importantly, only a handful of papers—most of them with a specific geographical scope—consider that different adaptation possibilities may lead to different impacts on energy demand, which is an important prerequisite if the impact of adaptation on energy demand is to be lowered and maladaptation to be avoided. The reviewed papers study for the most part similar options, and most adaptation possibilities are conversely studied by just one or two papers.